Racial/Ethnic Disparities in Costs, Length of Stay, and Severity of Severe Maternal Morbidity. (20th August 2020) - Phibbs, C.; Lorch, S.; Schmitt, S.; Main, E.; Kozhimannil, K.; Leonard, S.; Phibbs, C.
Abstract : Research Objective: Similar to maternal mortality, the United States has experienced increases in the rates of severe maternal morbidity (SMM) and has pronounced racial/ethnic disparities in SMM, with non‐Hispanic Black (NHB) women having twice the rate as non‐Hispanic White (NHW) women. This study further examined these racial/ethnic disparities, looking for differences in costs, lengths of stay (LOS), and severity of SMM. Study Design: Secondary data analysis was performed using the CDC definition of SMM, including readmissions up to 42 days postpartumAUTHOR: Please confirm if the edits made in the sentence 'Secondary data analysis…up to 42 days postpartum' convey the intended meaning.. GLM models with a gamma distribution and a log link, with and without hospital fixed‐effects, were used to estimate the effect of SMM on costs and LOS, controlling for race/ethnicity, cesarean delivery, type of insurance, parity, maternal age and BMI, multiple births, and an obstetric severity index. Population Studied: California linked birth certificate‐patient discharge data for 2009‐2011. About 200 000 were excluded for missing charge data (almost all insured by Kaiser Permanente). Cost‐to‐charge ratios were used to estimate costs (including readmissions) after adjusting for inflation to December 2017 dollars. Mean DRG‐specific reimbursement was used to estimate physician payments. The final N = 1 262 862. Principal Findings: SMM was observed in 1.34% of NHW and 2.62% of NHB. Adjusting for delivery method, among those deliveries with SMM, NHB women also had 38% longer LOS (5.1 vs 3.7 days) and 23% higher average costs per case ($19 507 vs $15 879) compared to NHW women. There were small racial/ethnic differences in the rates for the specific groups of diagnoses in the CDC definition of SMM, but NHB women had higher costs and LOS per case within almost all of these groups. Adjusting for risk, NHB women with SMM had costs that were 22% higher without and 17% higher with hospital fixed‐effects. For LOS, these were 21% and 20%, respectively. These effects were slightly smaller (15% and 12% for costs and 14% and 13% for LOS, respectively) when the different indicators of SMM were controlled for, indicating that NHB women were somewhat more likely to have more serious types of SMM. Asian women experienced added costs that were similar to NHB women in models without hospital fixed‐effects, but these differences were much smaller in the fixed‐effects models. Conclusions: There are racial/ethnic disparities in the per‐case costs and LOS among patients with SMM. The moderation of these effects for NHB women in the fixed‐effects models indicates that some of the elevated costs and LOS are due to disparate quality of care at hospitals more likely to treat NHB women. This effect is even more pronounced for Asian women. Implications for Policy or Practice: These results indicate a key policy role for facility‐based improvements and interventions. Additionally, the moderation of overall effects when the type of SMM is controlled for indicates that some of the added costs and LOS for NHB and Asian women are due to a higher prevalence of more serious types of SMM. This individual risk could also be shaped by broader social determinants of health as well as policies. Initiatives to reduce racial disparities in SMM should account for both individual risk (clinical complexity) and structural risk (hospital‐ and system‐level factors). Primary Funding Source: National Institutes of Health.